Tabernines A-C, beta-carbolines from the leaves of Tabernaemontana elegans. - Mansoor, T.A. (2018)
Three novel beta-carboline indole alkaloids (1-3) have been isolated from a MeOH extract of the leaves of Tabernaemontana elegans. The structures were established by means of spectroscopic techniques including 2D NMR experiments. Compounds 1 and 2 contain a two-carbon unit, attached to a structurally related beta-carboline skeleton, as part of an additional six-membered ring in 1 and a seven-membered ring in 2. To the best of our knowledge, this is the first report of beta-carboline indole alkaloids from the genus Tabernaemontana. Compounds 1-3 were evaluated for their ability to modulate multidrug resistance in mouse lymphoma cell lines. Compounds 1 and 3 exhibited a weak activity.